Tantangan dan Solusi dalam Implementasi SIMRS di Rumah Sakit Pemerintah di Indonesia - Dinda Natasya Putri; Sri Hajijah Purba; Khalisha Layana; Khoirunnisa Lubis (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The implementation of Hospital Management Information System (SIMRS) in Indonesian government hospitals has had a significant impact on improving the efficiency and quality of health services. However, the implementation process of SIMRS faces various challenges, including limited technological infrastructure, resistance to change from staff, and a lack of professionals in the field of information technology (IT). This study aims to identify the challenges faced in the implementation of SIMRS in Indonesian government hospitals, as well as the solutions implemented to overcome them, with case studies in Dr. Sardjito General Hospital, Dr. Soetomo General Hospital, and Sanglah General Hospital. The findings show that the main challenges related to infrastructure, such as outdated hardware and limited internet connectivity, affect the smooth implementation of SIMRS. The solutions implemented include improving IT infrastructure, intensive training for staff, and recruiting IT experts to support the system. In addition, other solutions such as strengthening data security protocols to protect patient information are also important to maintain public trust. Despite the significant challenges, these hospitals have successfully overcome these obstacles and provide examples of successful SIMRS implementation. This success can improve the efficiency, transparency, and quality of health services which in turn strengthen public trust in government health services.